Cultural patterns and way of learning in mapuche children from La Araucanía - Alonqueo, Paula; Muñoz, Ana María; Hidalgo-Standen, Carolina (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2024)
This paper presents the main results of research conducted with rural Mapuche children from La Araucanía, Chile, at the Cognition and Culture Laboratory, Kimkantun. The objective of this work was to describe cultural practices that occur in the participants' homes and at school. A mixed multilevel design was used. The research team made visits to the children's families and to the school, which were recorded in field notes and videos. A textual and conceptual analysis of the contexts in which the Mapuche children deployed their patterns of cultural interaction was carried out. The videos were analyzed using a micro- ethnography technique. In addition, to assess third-party attention, the children were invited to build a toy. The results show that the children display their own cultural patterns of interaction that are expressed through silence, attention to others, and the primacy of collaboration. These behaviors are consistent with the Mapuche Kimeltuwün model of learning, and constitute a powerful resource for promoting the development of Mapuche children.